The Meaning of The Romantic Relationship for Husband and Wife Couples - Mevi Yulinda; Yanti Tayo; Wahyu Utamidewi (Peneliti.net, 2022)
Romantic relationships are voluntary interactions compared to other types of relationships with groups, these relationships differ in intensity, usually characterized by expressions of affection and expectations of sexual behavior. This study discusses the meaning of romantic relationships in married couples who are still students. The purpose of this study is to understand the meaning and motives of romantic relationships and the communication experience of married couples who are still students. This study uses a qualitative methodology with a phenomenological study. The results of this study found that (1) The motive of romantic relationships for married couples who are still students is a noble thing and must be maintained as well as possible because involves interest, commitment, and intimacy in the form of verbal and nonverbal communication carried out in everyday life. (2) The meaning of the romantic relationship of a married couple who is still a student is also found in involvement, control, sharing of time and activities as well as the presence of attention and trust. (3) The experience of communication between husband and wife carried out by married couples who are still students is a form of interpersonal communication in the form of verbal and nonverbal communication, with the aim of sharing stories, feelings and giving attention.